Recovery of Burned Peatland: Revegetation Pattern Planning in Palm Oil Concession, South Sumatra - Supriyadi, Supriyadi; Priatna, Satria Jaya; Prayitno, Muhammad Bambang; Harun, Muhammad Umar; Nur Khakim, Mokhamad Yusup; Mohadi, Risfidian (Program Pascasarjana Universitas Sriwijaya, 2023)
Peatland ecosystems can recover from fire disasters through ecological succession, revegetation or both. In the context of oil palm plantations, revegetation planning for peatlands aims to restore the hydrological and carbon storage functions of peatlands, as well as to continuously increase the diversity of local vegetation by minimizing engineering activities on the land. This study explores the factors that influence revegetation of peatlands, identifies the distribution of water table levels as the main determinant. The water table levels, which vary from approximately 10 cm to 110 cm, correlate with topographic conditions and significantly impact vegetation survivability. The dominant plant species in the study area is Purun (Eleociharis dulcis), occupying approximately 44.5% of the total area. Other adaptable vegetation types, such as Gelam (Melaleiuca spp.) and Perepat (Combretocarpus rotundiatus), are considered suitable for propagation and planting as part of the peatland revegetation program. The study recommends prioritizing revegetation in areas with low vegetation diversity. Planting in areas with deep groundwater levels (60-80 cm) is recommended during the dry or humid months (June to September), while planting in areas with shallow groundwater levels (0-40 cm) is better conducted in the rainy season (October to December).